Periprosthetic infections: How do we diagnose and treat? Results of an online survey and comparison with international recommendations. Issue 5 (17th June 2021) - Otto‐Lambertz, Christina; Glauner, Andreas; Yagdiran, Ayla; Eysel, Peer
Abstract : Objective: Endoprosthetic replacement surgery of hip and knee joints is widely performed, but always carries the risk of developing periprosthetic infection (PPI). Treatment of PPI is lengthy and demanding for the patient, often involving multiple surgeries as well as lengthy drug therapies. Remediation is not always successful despite extensive therapy. Methods: An online survey was used to investigate whether the therapeutic measures implemented in German hospitals are based on international treatment recommendations. For this purpose, German physicians who regularly treat periprosthetic infections in their clinics were asked to complete an online questionnaire. The questionnaire asked about internal hospital procedures. These were then compared with international recommendations. Results: With a response rate of 10.9%, the questionnaire shows agreement with the international recommendations in large parts of the operative and medicinal procedures. In preoperative imaging for example, two‐plane radiographs are the standard. Similarly, the participants' approach to preoperative specimen collection, incubation time, and operative management (regarding one‐ or two‐stage approach to septic joint) reflects the recommendations. Deviations were particularly evident in the area of laboratory diagnostics, where the erythrocyte sedimentation rate (ESR) is determined in only 17.1%, contrary to the recommendations. Whereas procalcitonin (PCT) and blood culture sampling takes place regularly. Clear differences emerges in the use of drains, which, contrary to the recommendations, are used very regularly (almost 70%). In this survey, the time intervals between the onset of infection symptoms and the start of therapy (prosthesis‐preserving therapy) is shown to be longer than recommended internationally. Conclusion: In summary, however, the recommended approaches of the international groups in most respects are followed, a high willingness of respondents to collaborate with local infectious disease specialists demonstrates the complexity of the disease. Abstract : When a prosthesis change is required, the majority of clinics follow the international guidelines and requirements, for example concerning the two‐stage revision (black graph), not one stage exchanges (gray graph).